Bibliometric analysis and review of food waste management via sustainable approaches - U. Danya; M. Kamaraj; P. Suresh Babu; J. Aravind (Global Journal of Environmental Science and Management)
The escalating global food waste crisis presents both a challenge and an opportunity for sustainable development. Every year, millions of tons of food are wasted, contributing to environmental degradation and resource inefficiency. This wasted food not only represents a loss of valuable resources but also contributes to significant greenhouse gas emissions when disposed of in landfills. In response to this pressing issue, food waste valorization biorefineries have emerged as a promising solution, transforming waste into valuable bioproducts through innovative biotechnological processes. This review critically examines recent trends in food waste biorefining, focusing on the latest advancements in microbial and enzymatic conversion technologies. Various valorization pathways that convert food waste into biofuels, biochemicals, and bio-based materials are explored, thereby integrating principles of the circular economy to minimize waste and maximize resource utilization. Key developments in the field include the optimization of microbial consortia for enhanced degradation and conversion efficiency, as well as the engineering of enzymes to improve specificity and activity. These advancements have led to significant improvements in the efficiency and feasibility of converting food waste into high-value products. The environmental benefits of these biorefineries are also discussed in depth, encompassing the reduction of greenhouse gas emissions, decreased reliance on fossil fuels, and the mitigation of environmental pollution. By diverting food waste from landfills and transforming it into renewable resources, these biorefineries play a crucial role in promoting environmental sustainability. Despite these advancements, several challenges remain. Feedstock variability affects process consistency, leading to fluctuations in product yield and quality. There is a need for process optimization to improve yield and cost-effectiveness, ensuring that biorefinery operations are economically viable at an industrial scale. Issues related to scalability and industrial implementation, such as the development of infrastructure and supply chains, also pose significant hurdles. By synthesizing current research, this review underscores the considerable potential of food waste biorefineries to contribute to sustainable agriculture and biocatalysis. Critical gaps in knowledge are identified, and areas for future research are proposed, such as developing robust and flexible biorefining systems capable of handling diverse feedstocks and integrating advanced biotechnological tools for process monitoring and control. The review also highlights the importance of interdisciplinary collaboration and public-private partnerships in driving innovation and commercialization in this field. Ultimately, this review aims to provide a comprehensive understanding of the current state of food waste biorefining and to offer a roadmap for future research and industrial implementation. By highlighting the role of these biorefineries in achieving sustainable development goals, the review emphasizes the need for continued research, technological innovation, and supportive policy frameworks. Through these efforts, food waste valorization biorefineries can play a pivotal role in creating a sustainable and resilient future, addressing both environmental and economic challenges posed by food waste.